The drivers, trends and dietary impacts of non-nutritive sweeteners in the food supply: a narrative review. Issue 2 (5th December 2021) - Russell, Cherie; Grimes, Carley; Baker, Phillip; Sievert, Katherine; Lawrence, Mark A.
Abstract: Poor diets, including excess added sugar consumption, contribute to the global burden of disease. Subsequently, many nutrition policies have been implemented to reduce added sugar intake and improve population health, including taxes, education, labelling and environmental interventions. A potential consequence of these policy actions is the substitution of added sugars with non-nutritive sweeteners (NNS) in a variety of foods and beverages. NNS are used to reduce the energy and sugar content of foods and beverages while maintaining their palatability. Evidence of the toxicological risks of NNS is inconsistent, though concerns have been raised over the potential substitution effects of ultra-processed foods containing NNS for whole foods. This review aimed to provide an overview of current NNS food supply and consumption patterns, assess added sugar-reduction policies and their impact on NNS, and determine the impact of NNS on food choice, energy intake and diet quality. NNS are widely available in a variety of products, though most commonly in carbonated beverages, dairy products, confectionery, table-top sweeteners and fruit drinks. However, the longitudinal trends of different product categories, and differences between geographies and economy-income levels, require further study. Few studies have examined NNS consumption trends globally, though an increase in NNS consumption in beverages has been observed in some regions. Research examining how the increased availability of low-sugar, NNS-containing products affects global dietary patterns is limited, particularly in terms of their potential substitution effects.